1999
DOI: 10.1038/sj.bmt.1701746
|View full text |Cite
|
Sign up to set email alerts
|

Influence of recombinant human granulocyte colony-stimulating factor (filgrastim) on hematopoietic recovery and outcome following allogeneic bone marrow transplantation (BMT) from volunteer unrelated donors

Abstract: Summary:Effects of recombinant human granulocyte colony-stimulating factor (rhG-CSF, filgrastim) on hematopoietic recovery and clinical outcome in patients undergoing allogeneic bone marrow transplantation (BMT) from volunteer unrelated donors (VUD) were analyzed retrospectively. Additionally, the influence of baseline patient and transplant characteristics on hematopoietic recovery was evaluated. From January 1994 to March 1996, 47 consecutive adult patients received VUD-BMT. GVHD prophylaxis was cyclosporin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 24 publications
6
37
1
Order By: Relevance
“…56,58,60,62 However, one retrospective study found a delayed engraftment by 2 days with the use of G-CSF vs observation in BMT patients. 55 The authors did not speculate on the reason for their contradictory result. In three RCTs in patients undergoing PBSCT, the time to plt engraftment was not significantly different in patients who received G-CSF vs those who did not; 12,57,61 this was considered level 1B evidence because of a combined number of o100 in each group.…”
Section: Review Of Literature: Allogeneic Transplantationmentioning
confidence: 99%
See 4 more Smart Citations
“…56,58,60,62 However, one retrospective study found a delayed engraftment by 2 days with the use of G-CSF vs observation in BMT patients. 55 The authors did not speculate on the reason for their contradictory result. In three RCTs in patients undergoing PBSCT, the time to plt engraftment was not significantly different in patients who received G-CSF vs those who did not; 12,57,61 this was considered level 1B evidence because of a combined number of o100 in each group.…”
Section: Review Of Literature: Allogeneic Transplantationmentioning
confidence: 99%
“…Three non-randomized studies evaluating outcomes in BMT patients showed similar findings. 55,58,62 However, one retrospective study found a slight but statistically significant delay in plt engraftment when G-CSF was used in both PBSCT and BMT patients. 60 This delay in plt engraftment in the study by Ringden et al 60 was presumed to be a result of G-CSF increasing plt aggregation and creating an accelerated intravascular consumption of plts.…”
Section: Review Of Literature: Allogeneic Transplantationmentioning
confidence: 99%
See 3 more Smart Citations